ACTINOMYCETES AS A SOURCE OF POTENTIAL ANTIMICROBIAL AND ANTIBIOFILM AGENTS - Setiawati Setiawati; Rizak Tiara Yusan (Fakultas Kedokteran Universitas Jenderal Soedirman, 2022)
Actinomycetes are Gram-positive bacteria, anaerobic or facultative with a fungal-like morphology, widely distributed in both waters and land. Actinomycetes are bacteria with the largest taxonomic unit with diverse phyla diversity related to morphology, physiology, and metabolic ability. Actinomycetes have been known to have many benefits in medicine, including antibiotics, antifungals, antivirals, and anticancer. The content of secondary metabolites produced by actinomycetes varies widely. Actinomycetes contain active compounds from the polyene, terpenoid, phenolic, polyketide, phenazine, piperazine, and non-polyene groups, which have been shown to have antibacterial, antifungal, and antibiofilm activities. Streptomycetes known produce most of the antibiotics. Many compounds have been isolated from actinomycetes have antimicrobial and antibiofilm activities. It can be developed for further research because there are no antibiofilm candidate drugs from actinomycetes that the FDA approved until now. This paper discusses the active compounds isolated from actinomycetes which have antibacterial, antifungal, and antibiofilm activities, and their mechanism of action.